ANALYSIS OF FINANCIAL REPORTING QUALITY (CASE STUDY IN THE COVID-19 PANDEMIC PERIOD) (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2024)
The COVID-19 pandemic outbreak has transformed every aspect of human life worldwide, including the financial sector. This study aims to examine the comparison of financial reporting quality before and during the COVID-19 pandemic period. The data for analysis were derived from the financial reports of the companies listed on the Indonesia Stock Exchange (IDX). For the case pre-pandemic, the data were obtained from 2016-2019 while those during the pandemic were in 2020 since the spread of the outbreak. The data analysis showed that the results varied on several research models. What is a going concern was assets impairment and firm size as the factors with a negative effect on the quality of financial reporting during the pandemic. However, the level of liquidity, contract modifications, and company growth had a positive impact on the quality of financial reporting during the pandemic. Generally, the financial reporting quality during the pandemic improved compared to that before the COVID-19 pandemic. Keywords: financial reporting quality, going concern, liquidity, impairment, contract modification, and fair value